GE_GERICHTE P/9412/2014 vom 11. Dezember 2017 - GE Cour de justice (2017)
SÉQUESTRE(MESURE PROVISIONNELLE) ; CONFISCATION(DROIT PÉNAL) ; TIERS NON IMPLIQUÉ ; PRINCIPE DE LA BONNE FOI ; SOUPÇON ; ALLOCATION AU LÉSÉ ; CONTRE-PRESTATION | CPP.263.al1; CPP.197.al1; CP.70.al1; CP.70.al2